A preliminary study on the integration of Naqli and Aqli knowledge: USIM experience in English for professionals course - Siti Salmiah Muhammad; Emelia Effendy; Mohd Muzhafar Idrus (Universiti Sains Islam Malaysia, 2024)
Proceeding iECNA 2016 (23-24 August 2016), Universiti Sains Islam Malaysia